GAMBARAN KADAR HEMOGLOBIN PADA PENDERITA DIABETES MELITUS KOMPLIKASI GINJAL - Putra Rahmadea Utami; Khairul Fuad (JURNAL KESEHATAN PERINTIS, 2018)
Diabetes Mellitus (DM) commonly known as diabetes is a disease characterized by persistent and varied hyperglycemia (elevated blood sugar), especially after eating. Diabetes mellitus is a state of chronic hyperglycemia with a variety of metabolic abnormalities due to hormonal disturbances, leading to various chronic complications of the eyes, kidneys, and blood vessels, with lesions in the basement membrane in examination with an electron microscope. Chronic complications of DM are impaired renal function with a high incidence rate of 20-40% which can inhibit the formation of erythropoietin as Hb formers and cause anemia.The purpose of this study was to determine hemoglobin levels in people with diabetes mellitus kidney complications. This research type is descriptive analitik, sample population in this research is patient with diabetes mellitus kidney complication with total sample 30 people, this research took place at RSUD Solok in February until march 2017.Data processed in a way of frequency distribution table, zingga in get the results of most people with diabetes mellitus kidney complications are below normal levels.